Abrasive pad and method of manufacturing the same

CN123022518APending Publication Date: 2026-10-30FUJIBO HLDG
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202580023728.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2025-03-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]另外,构成研磨垫的聚氨酯树脂一般为疏水性,因此与浆料的亲和性差,存在浆料难以滞留在研磨垫上的问题

Benefits of technology

[0030]根据本发明,能够得到启动性优异的研磨垫。另外,能够得到在被研磨物表面产生的划痕伤等缺陷得以减少的研磨垫。另外,能够得到具有高研磨速率的研磨垫。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022518A_ABST
    Figure CN123022518A_ABST
Patent Text Reader

Abstract

The present application provides an abrasive pad with excellent startability and a manufacturing method thereof. An abrasive pad including a resin sheet having a plurality of teardrop-shaped bubbles and having an abrasive surface for polishing a polished object, wherein a spin-spin relaxation time T 2s long component sequentially subtracts a free induction decay signal (FID) obtained by pulsed NMR, performs waveform separation, whereby the spin-spin relaxation time T 2s long to short sequentially into three components of amorphous phase, interface phase, and crystal phase, for the resin sheet, the difference ΔT 2s,15min between the spin-spin relaxation time T 2s,dry of the amorphous phase component of the resin sheet obtained from the measurement results of the relaxation time using pulsed NMR after the abrasive pad is polished for 15 minutes and the spin-spin relaxation time T 2s,15min of the amorphous phase component of the resin sheet obtained from the measurement results of the relaxation time using pulsed NMR in a dry state before the abrasive pad is polished is 0.35 ms or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to polishing pads and methods for manufacturing the same. In particular, it relates to polishing pads for polishing silicon, hard disks, mother glass for liquid crystal displays, and semiconductor devices, and methods for manufacturing the same. Background Technology

[0002] Materials such as optical materials, semiconductor devices, hard disks, and glass substrates require flat surfaces, therefore polishing pads are used for free abrasive grinding. Free abrasive grinding is a method of polishing the surface of the workpiece by supplying a slurry (polishing fluid) containing abrasive particles between the polishing pad and the workpiece.

[0003] Semiconductor devices are polished using the so-called Chemical Mechanical Polishing (CMP) method. This method utilizes the chemical components contained in the polishing slurry to enhance the mechanical polishing (surface removal) effect caused by the relative motion between the polishing agent and the object being polished, resulting in a high-speed and smooth polished surface.

[0004] Polishing pads are broadly classified into two types: polishing pads that use resin sheets formed by a wet film-forming method as the polishing layer (soft polishing pads), and polishing pads that are formed by curing polyurethane through the reaction of prepolymer and curing agent (dry method) and then slicing them (hard polishing pads). Soft polishing pads have multiple teardrop-shaped large air bubbles within the resin sheet, making them softer than hard polishing pads and suitable for fine polishing of the workpiece.

[0005] Hard abrasive pads are harder and have a superior abrasive rate (amount abraded per unit time) compared to soft abrasive pads, and are therefore often used for the initial polishing of workpieces. On the other hand, abrasive pads that use resin sheets formed by wet film deposition as the abrasive layer are soft. For abrasive pads used in the polishing of semiconductor devices, etc., as the requirements for defect-free and planarization characteristics of the workpieces are increasing, the use of soft abrasive pads is increasing, especially in fine polishing processes.

[0006] Since soft abrasive pads are used for fine grinding, they are required to be abrasive pads that do not easily cause scratches on the surface of the workpiece during the grinding process. Patent Document 1 describes a method to improve the problem of scratches caused by the residue of film-forming aids in urethane resins formed by wet film-forming methods after solidification treatment. This method uses compounds with alcohol hydroxyl groups as film-forming aids, thereby reducing the amount of residual film-forming aids in the abrasive pad after wet film formation.

[0007] Furthermore, the polyurethane resin constituting the polishing pad is generally hydrophobic, resulting in poor affinity with the slurry and difficulty in retaining the slurry on the polishing pad. To address this issue, Patent Documents 2 and 3 describe methods that introduce hydrophilic ethylene oxide repeating units onto the surface of a polishing pad made of urethane resin by using a urethane prepolymer composed of a glycol having repeating units with ethylene oxide suspended in the side chain and a polyisocyanate, thereby improving the wettability of the polishing slurry on the polishing pad. Additionally, Patent Document 4 describes methods that polymerize polyurethane resin using a polyol blend containing the hydrophilic portion of repeating units of polyethylene glycol or ethylene oxide, thereby improving the defect rate without reducing planarization efficiency.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 2023-44910

[0011] Patent Document 2: Japanese Patent Application Publication No. 2007-63323

[0012] Patent Document 3: Japanese Patent Application Publication No. 2007-63324

[0013] Patent Document 4: Japanese Patent Application Publication No. 2018-43342 Summary of the Invention

[0014] The problem that the invention aims to solve

[0015] However, in CMP technology, from the perspective of improving productivity and yield, it is necessary to stabilize the grinding rate. In particular, the grinding rate at the start of grinding is lower than the grinding rate in the steady state, so it is necessary to further reduce the time spent on ineffective grinding (start-up processing time) until the grinding rate is approximately constant.

[0016] However, although the abrasive pad in Patent Document 1 uses a resin sheet formed by a wet film-forming method as the abrasive layer, its purpose is to reduce scratches by eliminating the presence of residual film-forming aids, which can cause agglomerates. It does not recognize the issue of start-up processing time as a problem.

[0017] The abrasive pads in Patent Documents 2 and 3 are hard abrasive pads that are cured by reacting a prepolymer with repeating units of ethylene oxide in the side chains with a curing agent (chain extender), and do not include abrasive pads containing resin sheets obtained by a wet film-forming method. In addition, Patent Documents 2 and 3 only measure the contact angle when water is dropped onto the resin surface, and do not address the issue of shortening the start-up time.

[0018] The polishing pad in Patent Document 4 is also a dry polishing pad that is cured by reacting a prepolymer containing a polyisocyanate compound with urethane bonds with a curing agent (chain extender), and is not a polishing pad containing a resin sheet obtained by a wet film-forming method. In addition, the purpose of the polishing pad in Patent Document 4 is to increase the defect rate without reducing the planarization efficiency, and it is not aimed at shortening the start-up time.

[0019] Thus, none of the patent documents 1 to 4 recognized the issue of start-up time for abrasive pads that use resin sheets formed by wet film deposition as abrasive layers.

[0020] The present invention was made in view of the above-mentioned problems, and its object is to provide an abrasive pad with excellent start-up properties that uses a resin sheet formed by wet film formation as an abrasive layer, and a method for manufacturing the same.

[0021] Methods for solving problems

[0022] The inventors conducted in-depth research and discovered that, in an abrasive pad containing a resin sheet with multiple teardrop-shaped bubbles as the abrasive layer, the relaxation time T of the amorphous phase component of the resin sheet, obtained by measuring the relaxation time using pulsed NMR, was [the result of this research]. 2s,15min The relaxation time T of the amorphous phase component of the resin sheet, obtained by measuring the relaxation time using pulsed NMR in the dry state before dressing the aforementioned polishing pad, is compared with that of the amorphous phase component of the resin sheet. 2s,dry The difference is ΔT 2s,15min The present invention was completed by achieving excellent start-up performance of the grinding pad with a startup time of more than 0.35 ms.

[0023] The present invention may include the following components.

[0024] [1] An abrasive pad comprising a resin sheet having a plurality of teardrop-shaped bubbles and an abrasive surface for abrading a workpiece, wherein the abrasive surface is obtained by least squares method from the spin-spin relaxation time T 2s Waveform separation is performed by successively subtracting the free induction decay signal (FID) obtained through pulsed NMR from the long components, thereby separating the waveforms according to the spin-spin relaxation time T. 2s The components are divided into three parts from longest to shortest: amorphous phase, interface phase, and crystalline phase. In this case, for the above-mentioned resin sheet, the relaxation time T of the amorphous phase component of the resin sheet is obtained by measuring the relaxation time using pulsed NMR after 15 minutes of conditioning of the above-mentioned polishing pad. 2s,15min The relaxation time T of the amorphous phase component of the resin sheet, obtained by measuring the relaxation time using pulsed NMR in the dry state before dressing the aforementioned polishing pad, is compared with that of the amorphous phase component of the resin sheet. 2s,dry The difference is ΔT 2s,15min It is above 0.35ms.

[0025] [2] The abrasive pad according to [1], wherein the resin sheet is a polyurethane sheet.

[0026] [3] According to the polishing pad described in [1] or [2], the relaxation time T of the amorphous phase component is obtained from the relaxation time measurement results using pulsed NMR at five time points when the polishing pad is respectively adjusted for 15 minutes, 30 minutes, 60 minutes, 90 minutes and 120 minutes. 2s The deviation of the value is SD(T) 2s,15-120min (less than 0.05ms)

[0027] [4] The polishing pad according to any one of [1] to [3], wherein the relaxation time T of the amorphous phase component is obtained by measuring the relaxation time using pulsed NMR after the polishing pad has been prepared for 2 hours. 2s,120min The relaxation time T of the amorphous phase component, obtained by measuring the relaxation time using pulsed NMR in the dry state before dressing the aforementioned polishing pad, is compared with that of the amorphous phase component. 2s,dry The difference is ΔT 2s,120min It is above 0.35ms.

[0028] [5] The polishing pad according to any one of [1] to [4], wherein when the polishing pad is trimmed, the trimming time required for the relaxation time value of the amorphous phase component obtained from the relaxation time measurement result using pulse NMR to reach 0.8 ms or more is within 15 minutes.

[0029] Invention Effects

[0030] According to the present invention, a polishing pad with excellent start-up performance can be obtained. Furthermore, a polishing pad that reduces defects such as scratches on the surface of the workpiece can be obtained. Additionally, a polishing pad with a high polishing rate can be obtained. Attached Figure Description

[0031] Figure 1 This is a scanning electron microscope image of a resin sheet (polyurethane sheet) formed by a wet film-forming method, containing multiple teardrop-shaped bubbles and multiple roughly spherical microbubbles smaller than the teardrop-shaped bubbles, and including the interconnected bubbles.

[0032] Figure 2 This is a schematic diagram showing the time-free induction decay signal curve measured by pulse NMR and the curves when the least squares method is used to separate the waveform of the curve into amorphous phase (L composition), interface phase (I composition), and crystalline phase (S composition) based on the difference in spin-spin relaxation time.

[0033] Figure 3This is a graph showing the change in relaxation time of the amorphous phase components relative to the dressing time when the polishing pads of Examples 1-3 and Comparative Examples 1-2 were dressed, as determined by pulse NMR.

[0034] Figure 4 This is a graph showing the change in the proportion of amorphous phase components relative to the trimming time when the polishing pads of Examples 1-3 and Comparative Examples 1-2 were trimmed using pulsed NMR.

[0035] Figure 5 This is a graph showing the change in polishing rate relative to the number of wafers processed when polishing silicon wafers with TEOS (tetraethoxysilane) film using polishing pads from Examples 1-3 and Comparative Examples 1-2.

[0036] Figure 6 This is a graph showing the change in polishing rate relative to the number of wafers processed when polishing silicon wafers with TEOS (tetraethoxysilane) film using polishing pads from Comparative Examples 1-2.

[0037] Figure 7 This is a graph showing the change in polishing rate relative to the number of wafers processed when polishing silicon wafers with TEOS (tetraethoxysilane) film using polishing pads from Examples 1-2 and Comparative Example 1.

[0038] Figure 8 This is a graph showing the change in polishing rate relative to the number of wafers processed when polishing silicon wafers with TEOS (tetraethoxysilane) film using polishing pads from Example 3 and Comparative Example 2.

[0039] Figure 9 This is a graph showing the change in defect count relative to the number of wafers processed when polishing a silicon wafer with a Cu film using the polishing pads of Examples 1-3 and Comparative Example 1.

[0040] Figure 10 This is a graph showing the results of determining the components contained in the resin tablet of Comparative Example 1 using gas chromatography-mass spectrometry (GC-MS).

[0041] Figure 11 This is a graph showing the results of determining the components contained in the resin tablet of Example 3 using gas chromatography-mass spectrometry (GC-MS). Detailed Implementation

[0042] The following describes a method for carrying out the present invention.

[0043] <<Abrasive Pad>>

[0044] The polishing pad of the present invention comprises a resin sheet having multiple teardrop-shaped air bubbles. The polishing pad of the present invention is used for polishing optical materials, semiconductor wafers, semiconductor devices, hard disk substrates, etc., and is particularly suitable for chemical mechanical polishing (CMP), especially for finishing polishing, of devices on semiconductor wafers with oxide layers, copper, or other metal layers formed thereon.

[0045] A resin sheet with multiple teardrop-shaped bubbles is formed by a wet film-forming method. Teardrop-shaped bubbles refer to bubbles formed within the resin sheet by the wet film-forming method (bubbles exhibiting anisotropy, with a structure where the diameter increases from the upper part of the resin sheet (the side in contact with the workpiece) towards the lower part), used to distinguish them from generally spherical bubbles formed by dry molding. In other words, the resin sheet with multiple teardrop-shaped bubbles of the present invention can be described as a resin sheet formed by a wet film-forming method.

[0046] Wet film-forming method refers to the following process: dissolving the film-forming resin in an organic solvent, coating the resin-containing solution onto a sheet-like substrate, and then passing it through a coagulation solution containing the dissolved organic solvent but not the resin to displace the organic solvent, causing it to solidify and dry, thus forming a foamed layer. Typically, when manufacturing resin sheets using the wet film-forming method, multiple large, roughly teardrop-shaped air bubbles (teardrop-shaped bubbles) are generated inside the resin sheet.

[0047] Dry molding refers to a method of curing polyurethane by reacting a prepolymer containing a polyisocyanate compound with urethane bonds with a curing agent and a foaming agent. The foam is then sliced ​​into sheets to form a grinding pad. This dry molding method produces grinding pads with a hard grinding layer, containing relatively small, roughly spherical air bubbles within the foam. This creates openings on the grinding surface of the pad formed from the slices, allowing the slurry to be retained during grinding.

[0048] A resin sheet with multiple teardrop-shaped bubbles can contain multiple interconnected bubbles. These interconnected bubbles comprise a teardrop-shaped bubble and multiple generally spherical microbubbles smaller than the teardrop-shaped bubble, which are interconnected. (Ref.) Figure 1 ).

[0049] In this specification and claims, the resin sheet is preferably a polyurethane sheet. A polyurethane sheet refers to a sheet material whose main component is polyurethane resin (50% or more by mass of all resin constituting the resin sheet, preferably 70% or more by mass, more preferably 80% or more by mass, even more preferably 85% or more by mass, even more preferably 90% or more by mass, and even more preferably 95% or more by mass of polyurethane resin, which can be 100% by mass), and is clearly distinguished from sheets whose main component is other resins (such as silicone resin).

[0050] Furthermore, the resin sheet preferably does not contain fluorinated waterproofing agents with polyfluoroalkyl groups, more preferably it does not contain fluorinated waterproofing agents, even more preferably it does not contain fluorinated waterproofing agents, silicone waterproofing agents, or hydrocarbon waterproofing agents, and most preferably it does not contain any waterproofing agent. As a waterproofing agent, the waterproofing agent described in Japanese Patent Application Publication No. 2022-156160 can be cited as an example.

[0051] In this specification and claims, the polishing layer refers to a layer having a surface (polishing surface) that contacts and polishes a workpiece such as a semiconductor device. The polishing pad of this invention may also have other layers, such as a buffer layer, on the side of the polishing layer opposite to the polishing surface.

[0052] <<First-Type Abrasive Pad>>

[0053] The first aspect of the present invention is an abrasive pad comprising a resin sheet having a plurality of teardrop-shaped bubbles and having an abrasive surface for abrading the workpiece, wherein the abrasive pad is obtained by least squares method from the spin-spin relaxation time T. 2s Waveform separation is performed by successively subtracting the free induction decay signal (FID) obtained through pulsed NMR from the long components, and thus, according to the spin-spin relaxation time T... 2s The resin sheet is divided into three components from longest to shortest: amorphous phase, interface phase, and crystalline phase. In this case, the relaxation time T of the amorphous phase component of the resin sheet is determined by pulsed NMR after the abrasive pad has been prepared for 15 minutes. 2s,15min The relaxation time T of the amorphous phase component of the resin sheet, obtained by measuring the relaxation time using pulsed NMR in the dry state before dressing the polishing pad, is compared with that of the amorphous phase component of the resin sheet. 2s,dry The difference, i.e. ΔT 2s,15min It is above 0.35ms.

[0054] In this specification, the dressing of the grinding pad used for determining relaxation time using pulse NMR can be performed using a dressing device and slurry under the following dressing conditions.

[0055] (Revision conditions)

[0056] Grinding pad rotation speed: 30 rpm

[0057] Slurry: Colloidal silica aqueous solution

[0058] Slurry flow rate: 80 mL / min

[0059] Dresser rotation speed: 30 rpm

[0060] Dressing pressure: 10N.

[0061] The above-mentioned trimming process is described in detail. First, the grinding pad is placed on the grinding platform of the grinder. Using slurry and a trimmer, the trimmer and grinding pad are rotated at a trimming pressure of 10N, a rotation speed of 30rpm for the trimmer, and a rotation speed of 30rpm for the grinding pad. While trimming the grinding pad, slurry is dripped into the center of rotation of the grinding pad at a rate of 80mL for 1 minute.

[0062] As a dressing tool, for example, a 3M diamond dressing tool, model "A188", can be used.

[0063] As a slurry, an aqueous solution of colloidal silica can be used, for example. An example is an aqueous solution of colloidal silica stock solution (silica concentration of 14-16 wt%):water = 1:3 (mass ratio).

[0064] In this specification, a "dry state before dressing" grinding pad refers to a grinding pad that is not dressed and is not exposed to liquids such as water or slurry. Preferably, a "dry state before dressing" grinding pad refers to a grinding pad that is not dressed and is not exposed to liquids such as water or slurry, and is placed at a temperature of 25°C and a relative humidity of 50% for 48 hours.

[0065] (Pulse NMR)

[0066] Pulse NMR is also known as TD-NMR. Pulse NMR is measured using a pulse NMR apparatus, employing the solid echo method with a 90° pulse duration of 0.5 s, a repetition time of 4 s, a cumulative number of 128 times, and a temperature of 40°C.

[0067] Regarding the solid echo method, since it is well-known, detailed explanations are omitted. It is mainly used for the determination of samples with short relaxation times, such as glassy and crystalline polymers. In methods that apparently eliminate the dead time, if a 90° pulse is applied to the X-axis direction by applying two 90° pulses with a 90° phase change (90°x-τ-90°y pulse method), a free induction decay (FID) signal is observed after the dead time. If a second 90° pulse is applied to the Y-axis direction during the time τ when the FID signal does not decay, an echo appears at t = 2τ with the magnetization directions aligned. The resulting echo can approximate the FID signal after the 90° pulse.

[0068] The method of resolving the correlation between physical properties, phase separation structure, and composition from pulsed NMR analysis results is well known. Waveform separation is achieved by subtracting the free induction decay (FID) signal obtained from pulsed NMR sequentially from components with long spin-spin relaxation times T2, starting with those with long T2. This results in three components: the component with the long relaxation time is the highly mobile component (amorphous phase), the component with the short relaxation time is the less mobile component (crystalline phase), and the intermediate component is defined as the interface phase (used for analysis when it is difficult to distinguish between interface and amorphous phase components). The compositional amount (existence ratio) of each component is calculated using formulas based on Gaussian and Lorentzian functions (e.g., see "Phase Separation Structure Analysis of Polyurethane Resins Based on Solid-State NMR (High-Resolution NMR and Pulsed NMR)" (DIC Technical Review N.12, pp.7-12, 2006)).

[0069] (Spin-spin relaxation time)

[0070] In this invention, the relaxation times and proportions of the crystalline phase, interface phase, and amorphous phase components in a resin sheet obtained by pulsed NMR can be determined as follows.

[0071] First, four samples, each approximately 20 × 10 mm in size, were placed in a 1 cm diameter glass tube and then placed in a magnetic field. The macroscopic relaxation behavior of the magnetization after applying a high-frequency pulsed magnetic field was measured. Figure 2 As shown, the free induction decay (FID) signal was obtained (horizontal axis: time (milliseconds), vertical axis: free induction decay signal). The initial value of the obtained FID signal is proportional to the number of protons in the sample. When there are three components in the sample, the FID signal is the sum of the response signals of the three components. On the other hand, due to the differences in the mobility of the components in the sample, the decay rate of the response signal is different between the components, and the spin-spin relaxation time T2 is different. Therefore, it is possible to separate them into three components by the least squares method, which are respectively identified as amorphous phase, interface phase, and crystalline phase in descending order of spin-spin relaxation time T2 (refer to...). Figure 2 Amorphous phases are components with high molecular mobility, while crystalline phases are components with low molecular mobility; the components in between are called interface phases.

[0072] After obtaining the FID signal, a fitting process is performed to separate the FID signal into signals for three components with different kinematic properties (crystalline phase, interface phase, and amorphous phase). In the fitting process, the BRUKER "TD-NMRAnalyzer" software is used. Following the product manual, the obtained relaxation curves are fitted using the following formula 1. The ratio and relaxation time of each component are calculated from the curves obtained from the measurements of the three components. The fitting is performed in two stages. First, as the first stage, the FID signal in the measurement time interval of 0.15–2.0 ms is fitted using a single component (i.e., only the amorphous phase component). The FID signal of the aforementioned single component (amorphous phase component) in the interval of 0–2.0 ms is calculated (the FID signal of the aforementioned single component (amorphous phase component) is also calculated for the interval of 0–0.15 ms through fitting). Next, as the second stage, the waveform obtained by fitting in the first stage is subtracted from the overall FID signal of the three components in the measurement time interval of 0~2.0 ms. The subtracted waveform is then used as two components (i.e., the crystalline phase and the interface phase after removing the amorphous phase from the three components of crystalline phase, interface phase, and amorphous phase) for fitting. In this way, the FID signals of the crystalline phase and the interface phase can be separated from each other.

[0073] It should be noted that in this embodiment, the Weibull coefficients are set to W(1) = 2.0, W(2) = 1.0, and W(3) = 1.0 according to the relaxation time T2 from short to long for fitting.

[0074] In the first stage, the reason for fitting the FID signal in the measurement time range of 0.15~2.0 ms using only the amorphous phase composition is that the amorphous phase composition has a longer relaxation time compared to the crystalline phase composition and the interface phase composition (refer to...). Figure 2 FID signals with a measurement time of 0.15 ms or longer are considered to originate from the amorphous phase component. By subtracting the waveform obtained in the first stage from the second stage, FID signals consisting only of the crystalline and interface phases are obtained. Therefore, by fitting these two components, the waveforms of the crystalline and interface phase components can be determined more accurately.

[0075] This analytical method, by dividing the number of components used for fitting and the analytical interval, can more effectively obtain the characteristics of amorphous phase components with long relaxation times.

[0076] Formula 1

[0077]

[0078] Here, I(t) represents the fitting strength at time t, a iT(n) represents the intensity factor of the nth component, T2(n) represents the relaxation time of the nth component, and W(n) represents the Weibull coefficient of the nth component.

[0079] (ΔT 2s,15min )

[0080] In the first aspect of the present invention, a resin sheet is used, the relaxation time T of the amorphous phase component of the resin sheet is obtained by measuring the relaxation time using pulsed NMR after the abrasive pad has been prepared for 15 minutes. 2s,15min The relaxation time T of the amorphous phase component of the resin sheet, obtained by measuring the relaxation time using pulsed NMR in the dry state before dressing the aforementioned polishing pad, is compared with that of the amorphous phase component of the resin sheet. 2s,dry The difference is ΔT 2s,15min It is greater than 0.35ms. ΔT 2s,15min Preferably, the ms time is 0.36ms or more, more preferably 0.38ms or more, and even more preferably 0.40ms or more.

[0081] By using resin sheets with the above-mentioned properties, abrasive pads with excellent start-up handling properties can be obtained.

[0082] The reason why using resin sheets with the aforementioned properties can improve start-up processability may not be clear, but it can be speculated as follows. As mentioned above, by... 1 Regarding the spin-spin relaxation time T2 observed by H-pulse NMR, the crystalline phase has the fastest, followed by the interface phase and then the amorphous phase (therefore, the amorphous phase has the slowest relaxation time). The interface phase has a faster relaxation time than the amorphous phase and is considered to be an amorphous phase with constrained mobility. It is believed that if the slurry and the grinding surface of the grinding pad are fused, water molecules combine with part of the molecular chains that were constrained as the interface phase before the slurry was added, becoming a highly mobile amorphous phase component. Therefore, it can be considered that by adjusting ΔT... 2s,15min The values ​​are within the above range, so that within a shorter time after the slurry is added, most of the interfacial phase component before the slurry drips combines with water molecules from the slurry to become an amorphous phase component, and the slurry fuses with the resin sheet (penetrates into the interior of the resin sheet). Therefore, it is speculated that this can improve start-up performance.

[0083] Furthermore, by using resin sheets with the aforementioned properties, it is less likely to cause defects such as scratches on the surface of the workpiece being ground. Additionally, a high grinding rate can be achieved.

[0084] ΔT 2s,15min There is no particular limit to the upper limit; it can be below 0.60ms, below 0.55ms, or below 0.50ms.

[0085] (ΔT 2s,120min )

[0086] In the first aspect of the present invention, a resin sheet is preferably used that has the following relaxation time T: the relaxation time T of the amorphous phase component of the resin sheet obtained by measuring the relaxation time using pulsed NMR after 120 minutes of conditioning of the polishing pad. 2s,120min The relaxation time T of the amorphous phase component of the resin sheet, obtained by measuring the relaxation time using pulsed NMR in the dry state before dressing the aforementioned polishing pad, is compared with that of the amorphous phase component of the resin sheet. 2s,dry The difference, i.e. ΔT 2s,120min It is greater than 0.35ms. ΔT 2s,120min More preferably, the time is 0.36ms or more; even more preferably, 0.38ms or more; and even more preferably, 0.40ms or more.

[0087] If ΔT 2s,120min Within the above range, it is easy to obtain abrasive pads with excellent start-up performance.

[0088] ΔT 2s,120min There is no particular limit to the upper limit; it can be below 0.60ms, below 0.55ms, or below 0.50ms.

[0089] (SD(T 2s,15-120min ))

[0090] In the first aspect of the present invention, the relaxation time T of the aforementioned amorphous phase component is obtained from the relaxation time measurement results using pulsed NMR at five time points: 15 minutes, 30 minutes, 60 minutes, 90 minutes, and 120 minutes, respectively, when the abrasive pad is adjusted. 2s The deviation of the value is SD(T) 2s,15-120min Preferably less than 0.05ms. SD(T) 2s,15-120min More preferably, the ms is 0.04ms or less; even more preferably, the ms is 0.03ms or less; even more preferably, the ms is 0.025ms or less; even more preferably, the ms is 0.018ms or less; and even more preferably, the ms is 0.015ms or less.

[0091] SD(T 2s,15-120min Within the above range, it is easy to obtain abrasive pads with excellent start-up performance.

[0092] SD(T 2s,15-120min It can be obtained as shown in Equation 2 below.

[0093] Formula 2:

[0094]

[0095] (Percentage of amorphous phase component (%))

[0096] In this specification, the proportions of the crystalline phase, the interface phase (intermediate phase), and the amorphous phase are sometimes referred to as A1, A2, and A3 (%), respectively. Generally, the lower the proportion of the amorphous phase, the harder the polyurethane. Furthermore, the less interface phase there is, the more clearly the crystalline and amorphous phases are separated, tending to exhibit elastic properties that are less prone to deformation. Conversely, the more interface phase there is, the more indistinct the phase separation between the crystalline and amorphous phases becomes, tending to exhibit delayed elastic properties.

[0097] For the abrasive pad of the first aspect of the present invention, the proportion of the amorphous phase component, obtained from the relaxation time measurement using pulsed NMR after 15 minutes of abrasive pad preparation, is preferably 55% or more (in moles). More preferably, the proportion of the amorphous phase component is 58% or more, even more preferably 60% or more, and even more preferably 62% or more. There is no particular upper limit to the proportion of the amorphous phase component; it can be 75% or less, 70% or less, 68% or less, or 65% or less.

[0098] For the polishing pad of the first aspect of the present invention, the proportion of the amorphous phase component obtained from the relaxation time measurement using pulsed NMR after 30 minutes of polishing is preferably 58% or more, more preferably 60% or more, and even more preferably 62% or more. There is no particular upper limit to the proportion of the amorphous phase component; it can be 75% or less, 70% or less, 68% or less, or 65% or less.

[0099] For the polishing pad of the first aspect of the present invention, when polishing the polishing pad, the polishing time required for the relaxation time value of the amorphous phase component, obtained from the relaxation time measurement results using pulsed NMR, to reach 0.8 ms or more is preferably 15 minutes or less. More preferably, the polishing time required for the relaxation time value of the amorphous phase component to reach 0.8 ms or more is 10 minutes or less, and even more preferably, 5 minutes or less. If the polishing time required for the relaxation time value of the amorphous phase component to reach 0.8 ms or more is within the above range, a polishing pad with excellent start-up processing performance can be easily obtained.

[0100] <Polyurethane Resin>

[0101] The resin sheet preferably contains polyurethane resin. There are no particular restrictions on the type of polyurethane resin; any variety can be selected based on the intended use. For example, polyester-based, polyether-based, or polycarbonate-based polyurethane resins can be used.

[0102] Examples of polyester-based resins include polymers of polyester polyols such as ethylene glycol and butanediol (e.g., 1,4-butanediol) and adipic acid, and diisocyanates such as diphenylmethane-4,4'-diisocyanate. Furthermore, in addition to the above, polyols such as butanediol, trimethylolpropane, and triethanolamine can be further added to form polymers.

[0103] Among them, the polyester-based polyurethane resin is preferably a polyurethane resin that is a condensation product of a polyester polyol obtained by dehydration condensation of 1,4-butanediol and adipic acid, 1,4-butanediol, trimethylolpropane, and 4,4'-diphenylmethane diisocyanate (MDI). The molar ratio of 1,4-butanediol to trimethylolpropane is preferably 7:3 to 3:7, more preferably 7:3 to 5:5, and even more preferably 6:4.

[0104] Polyether-based resins include polymers of polyether polyols such as polytetramethylene ether glycol and polypropylene glycol with isocyanates such as diphenylmethane-4,4'-diisocyanate.

[0105] Polycarbonate-based resins include polymers of polycarbonate polyols and isocyanates such as diphenylmethane-4,4'-diisocyanate.

[0106] These resins can be commercially available, such as those produced by DIC under the trade name "CRISVON", Sanyo Chemical Industries under the trade name "SANPRENE", and Dai Nippon Seikou Chemical Industries under the trade name "RESAMINE", or they can be manufactured by oneself to have the desired properties.

[0107] (Modulus)

[0108] Modulus, or resin hardness, is an indicator of the hardness of a resin. It is the value obtained by dividing the applied load when a non-foamed resin sheet is stretched to 100% (twice its original length) by its cross-sectional area (hereafter referred to as 100% modulus). The higher the value, the harder the resin.

[0109] The polyurethane resin preferably has a 100% modulus of 1 to 10 MPa, more preferably 3 to 8 MPa, and even more preferably 4 to 7 MPa. If the 100% modulus is within the above range, it is easy to achieve both high grinding rate and defect suppression.

[0110] <Cellulose derivatives>

[0111] The resin sheet preferably contains a cellulose derivative. By including a cellulose derivative, the difference in relaxation time ΔT between the amorphous phase components is reduced. 2s,15min Larger sizes make it easier to obtain grinding pads with excellent start-up performance. Additionally, ΔT 2s,120min SD(T) 2s,15-120minThe trimming time required for the relaxation time of the amorphous phase component to reach 0.8 ms or more also tends to fall within the aforementioned range. Examples of cellulose derivatives include ester-based cellulose derivatives, ether-based cellulose derivatives, ether-ester-based cellulose derivatives, and aromatic cellulose derivatives. Among these, ester-based cellulose derivatives are more preferred. Examples of ester-based cellulose derivatives include acetylcellulose, triacetylcellulose, acetylbutylcellulose, diacetylcellulose, acetylpropylcellulose, ethylcellulose, cellulose propionate, cellulose butyrate, nitrocellulose, cellulose sulfate, cellulose phosphate, cellulose acetate butyrate, cellulose nitrate acetate, and cellulose acetate propionate. Among these, acetylcellulose, triacetylcellulose, acetylbutylcellulose, diacetylcellulose, and acetylpropylcellulose are preferred, and celluloses formed by esterifying part or all of the OH groups of cellulose (especially acetylcellulose with a degree of substitution of 2.41) are more preferred.

[0112] <Hydrophilic surfactants>

[0113] The resin sheet may contain a hydrophilic surfactant. When a hydrophilic surfactant is present, it is preferably included in the resin sheet along with a cellulose derivative. By including the hydrophilic surfactant along with the cellulose derivative, the relaxation time difference ΔT of the amorphous phase component is reduced. 2s,15min As it increases, it becomes easier to change ΔT. 2s,15min Adjusting the values ​​to the above range improves the ease of starting up the abrasive pad. Additionally, ΔT 2s,120min SD(T) 2s,15-120minThe dressing time required for the relaxation time of the amorphous phase component to reach 0.8 ms or more also tends to fall within the aforementioned range. The reason for this is not yet clear, but it is speculated as follows. It is speculated that by using hydrophilic surfactants with cellulose derivatives, the hydrophilic surfactants are difficult to remove from the coagulation bath during manufacturing, and most remain in the resin sheet. Therefore, more water molecules in the slurry can be captured in the hydrophilic surfactant of the resulting resin sheet, allowing the slurry to fuse with the resin sheet in a short time. Before the slurry penetrates and fuses into the interior of the grinding pad, uneven fusion occurs, making the grinding rate prone to instability. It is speculated that by making the slurry easier to fuse with the resin sheet, uneven fusion can be suppressed, shortening the time until the grinding rate of the grinding pad stabilizes (improving start-up performance). Examples of hydrophilic surfactants include anionic surfactants and cationic surfactants. Among these, anionic surfactants are preferred. Among anionic surfactants, sulfonate surfactants are more preferred. Examples of sulfonate surfactants include sodium lauryl sulfate, sodium alkylbenzene sulfonate, and sodium alkyl sulfosuccinate. Sodium alkyl sulfosuccinate is preferred. For example, sodium alkyl sulfosuccinate manufactured by DIC Corporation under the trade name CRISVON Assister SD-11 can be used as the sodium alkyl sulfosuccinate.

[0114] <Coagulation regulators and / or nonionic surfactants>

[0115] The resin sheet may contain a coagulation regulator and / or a nonionic surfactant. Examples of coagulation regulators include those composed only of carbon and hydrogen atoms (for example, hydrocarbons having 8 to 18 carbon atoms), such as paraffinic regulators, aromatic regulators, cycloalkane-based regulators, mineral oils, and synthetic oils. Paraffinic regulators (e.g., isoalkanes) and polybutene are preferred. For example, CRISVON Assister SD-8i manufactured by DIC Corporation can be used.

[0116] Examples of nonionic surfactants include polyalkylene glycol ethylene oxide, polyether-modified silicone oil, and copolymers of ethylene oxide and propylene oxide. Among these, copolymers of ethylene oxide and propylene oxide are preferred. For example, a copolymer of ethylene oxide and propylene oxide can be manufactured under the trade name CRISVON Assister SD-21 by DIC Corporation.

[0117] <Other Surfactants>

[0118] The resin sheet may contain surfactants other than those mentioned above. Examples of surfactants other than those mentioned above include carboxylic acid surfactants, sulfate surfactants, phosphate surfactants, ester surfactants, and alkanolamide surfactants.

[0119] <Polyol Compounds>

[0120] The resin sheet may contain polyol compounds. It should be noted that the polyol compounds referred to here are those added separately from the polyurethane resin during the preparation of the resin sheet and included within the resin sheet. Examples of polyol compounds include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2,3-propanetriol, 1,3-butanediol, 1,4-butanediol, and diethylene glycol. Diethylene glycol is preferred.

[0121] There is no particular limitation on the amount of polyol contained in the resin tablets, but it is preferably more than 100 ppm, more preferably more than 105 ppm, more preferably more than 110 ppm, even more preferably more than 115 ppm, and even more preferably more than 120 ppm. There is no particular limitation on the upper limit of the amount of polyol contained in the resin tablets, and it can be less than 1000 ppm, less than 800 ppm, less than 600 ppm, less than 400 ppm, less than 200 ppm, or less than 150 ppm.

[0122] Furthermore, when the polyol compound is diethylene glycol, the amount of diethylene glycol contained in the resin tablet is preferably more than 100 ppm, preferably more than 105 ppm, more preferably more than 110 ppm, even more preferably more than 115 ppm, and even more preferably more than 120 ppm. There is no particular upper limit to the amount of diethylene glycol contained in the resin tablet; it can be less than 1000 ppm, less than 800 ppm, less than 600 ppm, less than 400 ppm, less than 200 ppm, or less than 150 ppm.

[0123] When the resin sheet contains a coagulation regulator and / or a nonionic surfactant, it preferably contains a polyol compound. Furthermore, the polyol compound is preferably included in the resin sheet together with a cellulose derivative. By including the polyol compound together with the above-mentioned components, the difference in relaxation time ΔT of the amorphous phase components is reduced. 2s,15min As it increases, it becomes easier to change ΔT. 2s,15min Adjusting the values ​​to the above range improves the ease of starting up the abrasive pad. Additionally, ΔT 2s,120min SD(T) 2s,15-120minThe dressing time required for the relaxation time of the amorphous phase component to reach 0.8 ms or more also tends to fall within the aforementioned range. The reason for this is not yet clear, but it is speculated as follows: It is speculated that although coagulation regulators and / or nonionic surfactants are less hydrophilic than hydrophilic surfactants and lack the ability to capture water molecules, by using polyol compounds with cellulose derivatives, the polyol compounds are difficult to release into the coagulation bath during manufacturing, and most of them are contained within the resin sheet. Therefore, even with the use of coagulation regulators and / or nonionic surfactants, more water molecules in the slurry can be captured in the polyol compounds of the resin sheet, allowing the slurry to fuse with the resin sheet in a short time (slurry penetrates into the interior of the resin sheet), similar to the case when using hydrophilic surfactants. Before the slurry penetrates and fuses into the interior of the grinding pad, uneven fusion occurs, making the grinding rate prone to instability. It is speculated that by making the slurry easier to fuse with the resin sheet, uneven fusion can be suppressed, shortening the time until the grinding rate of the grinding pad stabilizes (improving start-up handling).

[0124] <Other Ingredients>

[0125] The abrasive pad of the present invention may also contain resin sheets other than those described above, without impairing the effects of the present invention. Examples of such other components include fillers such as carbon black.

[0126] (thickness)

[0127] The thickness of the resin sheet in the abrasive pad of the present invention is not particularly limited, for example, it can be used in the range of 0.60~1.20mm, preferably 0.70~1.10mm, more preferably 0.80~1.00mm.

[0128] (Polishing process)

[0129] Alternatively, the resin sheet can also be polished. In the polishing process, it is preferable to polish the skin layer side (grinding surface side) of the film-forming resin to make the thickness uniform. The grinding amount on the skin layer side based on the polishing process is preferably 50-200 μm, more preferably 80-200 μm, even more preferably 100-200 μm, and even more preferably 120-180 μm. If it is within this range, the thickness of the polyurethane resin sheet is uniform, which sufficiently ensures that the pores of the slurry are maintained on the grinding surface.

[0130] In addition, the resin sheet can also be grooved, embossed and / or holed (punched) on its grinding surface, with embossing being preferred.

[0131] (Other layers)

[0132] The abrasive pad of the present invention is based on the premise that the surface of the resin sheet (abrasive surface) is in contact with the workpiece being abraded, so there are no other resin layers on the abrasive surface of the resin sheet.

[0133] On the other hand, the abrasive pad of the present invention may have other resin layers (lower layer, support layer) bonded to the side of the resin sheet opposite to the surface of the workpiece being abraded (abrasive surface), or it may not have other resin layers bonded to it. The characteristics of the other resin layers are not particularly limited, but it is preferable to bond a layer that is harder than the resin sheet (higher hardness such as Shore A or Shore D). By providing a layer harder than the resin sheet, the influence of the fine unevenness of the abrasive platform on the shape of the abrasive surface can be avoided, further improving the flatness of the abrasive surface. Furthermore, by increasing the overall rigidity of the abrasive pad, wrinkles and other defects that occur when the abrasive pad is attached to the abrasive platform can be suppressed, improving workability.

[0134] <<Second Method of Grinding Pad>>

[0135] The second aspect of the present invention provides an abrasive pad comprising a resin sheet having a plurality of teardrop-shaped bubbles and an abrasive surface for abrading a workpiece, wherein the resin sheet comprises a cellulose derivative and a hydrophilic surfactant, or the resin sheet comprises a cellulose derivative, a coagulation regulator and / or a nonionic surfactant, and a polyol compound.

[0136] The components of the second type of polishing pad can be the same as those described in the first type of polishing pad. Regarding other aspects such as thickness and polishing treatment, the portions described in the first type of polishing pad can also be appropriately applied.

[0137] The abrasive pad of the present invention, by having the above-described combination, readily yields a abrasive pad with excellent start-up performance. The reasoning may not be clear, but it is speculated as follows. It is generally believed that while hydrophilic surfactants and polyol compounds have good compatibility with slurry, they also have good compatibility with coagulating liquid. Therefore, during the coagulation process, a large amount dissolves from the resin-containing solution composition into the coagulating liquid, and almost none remains in the resin sheet after the coagulation process. In contrast, it is believed that by using a combination of cellulose derivatives with hydrophilic surfactants and polyol compounds, the cellulose derivatives promote the formation of polyurethane resin nuclei during the coagulation process. The hydrophilic surfactants and polyol compounds are introduced into the nuclei along with the resin before dissolving into the coagulating liquid, increasing the amount of hydrophilic surfactants and polyol compounds remaining in the resin sheet after the coagulation process. Therefore, it is speculated that the increased hydrophilicity in the abrasive layer of the abrasive pad makes it easier to integrate with the slurry even in the initial stages of abrasive grinding, thus improving start-up performance.

[0138] Furthermore, it is believed that even when using coagulation regulators and nonionic surfactants, by combining them with highly hydrophilic polyol compounds, and further with cellulose derivatives, moderate hydrophilicity can be ensured, and dissolution into the coagulation bath can be prevented. Therefore, the hydrophilicity of the resin sheet after the coagulation process can be maintained at a high level. It is speculated that even in the early stages of grinding, it becomes easier to blend with the slurry, and start-up performance is improved.

[0139] Furthermore, the abrasive pad of the present invention, by having the above-described combination, is less prone to defects such as scratches on the surface of the workpiece being abraded. Additionally, a high abrasive rate can be achieved.

[0140] Furthermore, for the second type of polishing pad, it is preferable to perform waveform separation by successively subtracting the free induction decay signal (FID) obtained by pulsed NMR from the components with the longest spin-spin relaxation time T2 using the least squares method. This separates the components into three phases in descending order of spin-spin relaxation time T2: amorphous phase, interface phase, and crystalline phase. In this case, for the resin sheet, the relaxation time T of the amorphous phase component of the resin sheet is obtained by measuring the relaxation time using pulsed NMR after 15 minutes of polishing with the aforementioned pad. 2s,15min The relaxation time T of the amorphous phase component of the resin sheet, obtained by measuring the relaxation time using pulsed NMR in the dry state before dressing the aforementioned polishing pad, is compared with that of the amorphous phase component of the resin sheet. 2s,dry The difference is ΔT 2s,15min It is greater than 0.35ms. ΔT 2s,15min More preferably, the time is 0.36ms or more; even more preferably, 0.38ms or more; and even more preferably, 0.40ms or more.

[0141] ΔT 2s,15min There is no particular limit to the upper limit; it can be below 0.60ms, below 0.55ms, or below 0.50ms.

[0142] For the second type of polishing pad, preferably, the relaxation time T of the amorphous phase component is obtained by measuring the relaxation time using pulsed NMR after the polishing pad has been prepared for 15 minutes to 2 hours. 2s The deviation of the value is SD(T) 2s,15-120min Less than 0.05ms. SD(T) 2s,15-120min More preferably, the ms is 0.04ms or less; even more preferably, the ms is 0.030ms or less; even more preferably, the ms is 0.025ms or less; even more preferably, the ms is 0.018ms or less; and even more preferably, the ms is 0.015ms or less.

[0143] For the second type of polishing pad, preferably, the relaxation time T of the amorphous phase component is obtained by measuring the relaxation time using pulsed NMR after the polishing pad has been prepared for 2 hours. 2s,120min The relaxation time T of the amorphous phase component, obtained by measuring the relaxation time using pulsed NMR in the dry state before dressing the aforementioned polishing pad, is compared with that of the amorphous phase component. 2s,dry The difference is ΔT 2s,120min It is greater than 0.35ms. ΔT 2s,120min More preferably, the time is 0.36ms or more; even more preferably, 0.38ms or more; and even more preferably, 0.40ms or more.

[0144] ΔT 2s,120min There is no particular limit to the upper limit; it can be below 0.60ms, below 0.55ms, or below 0.50ms.

[0145] (use)

[0146] The polishing pad of the present invention is suitable for use as a polishing pad for polishing semiconductor devices, semiconductor wafers, silicon, glass, and other materials (chemical mechanical polishing (CMP)). Preferably, the polishing pad of the present invention is used as a polishing pad for semiconductor devices.

[0147] Furthermore, the abrasive pad of the present invention is applicable to chemical mechanical polishing of workpieces using abrasive slurry. Additionally, the abrasive pad of the present invention is also applicable to chemical mechanical polishing using slurry containing colloidal silica.

[0148] The abrasive pad of the present invention can be manufactured, for example, by the following method.

[0149] <<Manufacturing Methods of Grinding Pads>>

[0150] The method for manufacturing the abrasive pad of the present invention can be carried out using conventional wet film-forming methods. Preferably, the method for manufacturing the abrasive pad includes: a step of coating a resin solution composition comprising a polyurethane resin, a cellulose derivative, and a hydrophilic surfactant, or a resin solution composition comprising a polyurethane resin, a cellulose derivative, a coagulation regulator and / or a nonionic surfactant, and a polyol compound onto a film-forming substrate; and a step of immersing the film-forming substrate coated with the above-mentioned resin solution composition in a coagulation liquid to coagulate the above-mentioned resin solution composition, thereby forming a wet-formed resin sheet.

[0151] The following is a description of each process.

[0152] <Preparation Process>

[0153] In the preparation step, a resin solution composition containing polyurethane resin, cellulose derivative and hydrophilic surfactant is prepared, or a resin solution composition containing polyurethane resin, cellulose derivative, coagulation regulator and / or nonionic surfactant and polyol compound is prepared.

[0154] (Polyurethane resin)

[0155] The resin solution composition comprises a polyurethane resin that forms the material of the polyurethane abrasive pad. As the polyurethane resin, the polyurethane resins listed in the description of the abrasive pad can be used.

[0156] (cellulose derivatives)

[0157] The resin solution composition preferably contains a cellulose derivative. As a cellulose derivative, the cellulose derivatives listed in the description of the abrasive pad can be used. In the resin solution composition, relative to 100 parts by weight of polyurethane resin, it preferably contains 0.1 to 35 parts by weight of a cellulose derivative, more preferably 0.3 to 30 parts by weight, even more preferably 1 to 20 parts by weight, even more preferably 2 to 10 parts by weight, even more preferably 3 to 9 parts by weight, and even more preferably 4 to 8 parts by weight.

[0158] (Hydrophilic surfactant)

[0159] The resin solution composition may contain a hydrophilic surfactant. As the hydrophilic surfactant, the hydrophilic surfactants listed in the description of the abrasive pad can be used. In the resin solution composition, relative to 100 parts by weight of polyurethane resin, it is preferable to contain 0.1 to 35 parts by weight of the hydrophilic surfactant, more preferably 0.3 to 30 parts by weight, even more preferably 1 to 20 parts by weight, even more preferably 2 to 10 parts by weight, even more preferably 3 to 9 parts by weight, and even more preferably 4 to 8 parts by weight.

[0160] (Setting regulator)

[0161] The resin solution composition may contain a coagulation regulator. As a coagulation regulator, the coagulation regulators listed in the description of the abrasive pad can be used. In the resin solution composition, relative to 100 parts by weight of polyurethane resin, it is preferable to contain 0.1 to 35 parts by weight of a coagulation regulator, more preferably 0.3 to 30 parts by weight, even more preferably 1 to 20 parts by weight, even more preferably 5 to 20 parts by weight, even more preferably 8 to 18 parts by weight, and even more preferably 10 to 16 parts by weight.

[0162] (Nonionic surfactant)

[0163] The resin solution composition may contain a nonionic surfactant. As a nonionic surfactant, the nonionic surfactants listed in the description of the abrasive pad can be used. In the resin solution composition, relative to 100 parts by weight of polyurethane resin, it is preferable to contain 0.1 to 35 parts by weight of the nonionic surfactant, more preferably 0.3 to 30 parts by weight, even more preferably 1 to 20 parts by weight, even more preferably 2 to 10 parts by weight, even more preferably 3 to 9 parts by weight, and even more preferably 4 to 8 parts by weight.

[0164] In addition, in the resin solution composition, relative to 100 parts by weight of polyurethane resin, it is preferable to include 0.1 to 50 parts by weight of a total of coagulation regulator and nonionic surfactant, more preferably 0.3 to 40 parts by weight, even more preferably 1 to 30 parts by weight, even more preferably 5 to 30 parts by weight, even more preferably 8 to 25 parts by weight, even more preferably 10 to 25 parts by weight, and even more preferably 12 to 24 parts by weight.

[0165] (Polyol compounds)

[0166] The resin solution composition may contain a polyol compound. As the polyol compound, the polyol compounds listed in the description of the abrasive pad may be used. In the resin solution composition, relative to 100 parts by weight of polyurethane resin, it is preferable to contain 0.1 to 35 parts by weight of the polyol compound, more preferably 0.3 to 30 parts by weight, even more preferably 1 to 25 parts by weight, even more preferably 5 to 20 parts by weight, even more preferably 10 to 20 parts by weight, and even more preferably 12 to 18 parts by weight.

[0167] (Organic solvents)

[0168] As for the aforementioned organic solvents, any solvent capable of dissolving polyurethane resin and being water-miscible can be used without particular restrictions. Examples include N,N-dimethylformamide (DMF), methyl ethyl ketone, N,N-dimethylacetamide (DMAc), tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), and acetone. Among these, DMF or DMAc is preferred.

[0169] The organic solvent is preferably contained in the resin solution composition at a concentration of 10-50% by mass, more preferably 10-40% by mass, and even more preferably 20-40% by mass. At concentrations within the above range, the resin solution composition has suitable fluidity and can be uniformly coated onto the film-forming substrate in subsequent coating processes.

[0170] (Microporous control agent / density control agent)

[0171] In addition to the components mentioned above, the resin solution composition may also contain a micropore regulator or a density regulator. Water can be cited as a micropore regulator or density regulator.

[0172] Relative to 100 parts by weight of polyurethane resin, it preferably contains 0.1 to 35 parts by weight of microporous regulator / density regulator, more preferably 0.3 to 30 parts by weight, even more preferably 1 to 25 parts by weight, even more preferably 5 to 20 parts by weight, even more preferably 10 to 20 parts by weight, and even more preferably 12 to 18 parts by weight.

[0173] (Other ingredients)

[0174] Provided that the effects of the present invention are not impaired, the resin solution composition may further contain other components besides those described above. Other components listed in the description of the abrasive pad may be used as additional components.

[0175] The resin solution composition preferably does not contain fluorinated waterproofing agents with polyfluoroalkyl groups, more preferably does not contain fluorinated waterproofing agents, more preferably does not contain fluorinated waterproofing agents, organosilicon waterproofing agents, hydrocarbon waterproofing agents, and most preferably does not contain any waterproofing agent.

[0176] <Coating Process>

[0177] The resin solution composition obtained above is continuously coated onto a film-forming substrate in a substantially uniform manner at room temperature using, for example, a doctor blade coater or a reverse coater. At this time, the coating thickness (coating amount) of the resin solution composition can be adjusted by changing the gap (void) between the doctor blade coater and the film-forming substrate.

[0178] As a film-forming substrate, any substrate commonly used in this technical field can be used without particular restrictions. Examples of film-forming substrates include flexible films, nonwoven fabrics, and woven fabrics. Examples of flexible films include polyester films, polyolefin films, and other flexible polymer films. Examples of nonwoven fabrics and woven fabrics include nonwoven fabrics and woven fabrics impregnated with elastic resins. When using nonwoven fabrics or woven fabrics as film-forming substrates, in order to prevent the resin solution composition from penetrating into the film-forming substrate during coating, it is preferable to perform a pretreatment (sealing) by pre-immersing the substrate in water or an aqueous solution of an organic solvent (such as a mixture of DMF and water). Polyester films are preferred among these substrates.

[0179] <Solidation Process>

[0180] A film-forming substrate coated with a resin solution composition is immersed in a coagulation solution primarily composed of water, which is a poor solvent for polyurethane resin. By allowing the resin solution composition to solidify, a wet-formed resin sheet is formed.

[0181] As the coagulating liquid, water, or a mixture of water and a polar solvent such as DMF are used. Examples of polar solvents include water-mixed organic solvents used to dissolve polyurethane resins, such as DMF, DMAc, THF, DMSO, NMP, and acetone. Furthermore, the concentration of the polar solvent in the mixed solvent is preferably 0.5 to 30% by mass.

[0182] There are no particular restrictions on the temperature of the coagulation solution or the soaking time; for example, soaking at 5-80℃ for 5-60 minutes is sufficient.

[0183] In the coagulation process, the coating film (film-forming substrate coated with the resin solution composition) obtained in the coating process is immersed in a coagulation liquid (e.g., water, or a water-based solvent) that is a poor solvent for polyurethane resin, causing the coating film of the resin solution composition to coagulate and regenerate into a sheet with multiple internal foams. In the coagulation liquid, typically, firstly, a skin layer with a thickness of several μm is formed on the surface of the coated resin solution composition. This skin layer has micropores. Then, the organic solvent in the resin solution composition is replaced by the coagulation liquid, thereby causing the polyurethane resin to coagulate and regenerate into a sheet on one side of the film-forming substrate. Typically, the organic solvent is desolventized from the resin solution composition and replaced by the coagulation liquid, thereby forming bubbles on the underside of the skin layer (film-forming substrate side) in a substantially uniformly dispersed state. These bubbles have a pore size larger than the micropores formed in the skin layer and are approximately triangular in cross-section with rounded corners in the thickness direction of the sheet (teardrop-shaped bubbles), but the foaming structure is not limited to this.

[0184] In addition, the resulting sheet typically contains multiple interconnected air bubbles. These interconnected air bubbles consist of teardrop-shaped bubbles and multiple generally spherical microbubbles smaller than the teardrop-shaped bubbles, which are interconnected.

[0185] <Washing and Drying>

[0186] After the coagulation process, the wet-film-forming resin sheet obtained by coagulation in the coagulation bath can be peeled off from the film-forming substrate or cleaned and dried without peeling.

[0187] The residual organic solvent in the wet-film-forming resin sheet is removed through a cleaning process. Water can be used as the cleaning solution.

[0188] After cleaning, the wet-film-forming resin sheets can be dried. Drying can be performed using conventional methods, such as drying in a dryer at 80-150°C for approximately 5-60 minutes. After these steps, resin sheets can be obtained.

[0189] In the manufacturing method of the polishing pad of the present invention, the polishing surface of the resin sheet and / or the surface opposite to the polishing surface may be ground (polished) as needed. Additionally, groove processing, embossing, and / or hole processing (punching) may be performed on the polishing surface of the resin sheet, and a substrate may be bonded to the resin sheet. Furthermore, a light-transmitting portion may be provided in the resin sheet and / or the polishing pad.

[0190] There are no particular restrictions on the grinding method; grinding can be performed using well-known methods. Specifically, grinding using sandpaper can be cited as an example.

[0191] There are no particular restrictions on the shape of groove processing and embossing processing; for example, grid-shaped, concentric circle-shaped, and radial shapes can be given.

[0192] When a multi-layer structure is formed by bonding with a substrate, multiple layers can be bonded and fixed together by applying pressure as needed using double-sided tape, adhesive, etc. There are no particular restrictions on the double-sided tape and adhesive used; any double-sided tape and adhesive known in this technical field can be selected.

[0193] Then, double-sided tape is applied to the side of the resin sheet opposite to the grinding surface or the side of the substrate opposite to the side adhered to the resin sheet, and cut into a predetermined shape, preferably a circular plate, to complete the grinding pad of the present invention. There are no particular limitations on the double-sided tape; any double-sided tape known in the art can be selected and used.

[0194] <Grinding Method>

[0195] The grinding method of the present invention is a grinding method for a workpiece that includes the step of grinding the workpiece using a grinding pad. During grinding, the workpiece can be held in place using a retaining pad while being ground using the grinding pad.

[0196] When using the abrasive pad of the present invention, the abrasive pad is mounted on the abrasive platform of the abrasive machine with the abrasive surface of the resin sheet facing the workpiece. Then, while supplying abrasive slurry, the abrasive platform is rotated to abrade the workpiece surface. The abrasive machine can be either a single-sided abrasive machine or a double-sided abrasive machine. Hereinafter, as a specific example, the abrasive process when using a single-sided abrasive machine will be described.

[0197] First, the workpiece is held on the holding platform of the single-sided grinder. Next, a grinding pad is mounted on the grinding platform, which is positioned opposite the holding platform. Then, a slurry containing abrasive particles (grinding particles) is supplied between the workpiece and the grinding pad, and the grinding platform or holding platform is rotated while pressing the workpiece against the grinding pad at a specified grinding pressure, thereby grinding the workpiece by chemical mechanical grinding.

[0198] Examples of objects to be polished (held) include semiconductor devices, semiconductor wafers, silicon, and glass. Among these, semiconductor devices are preferred. Examples of materials for semiconductor devices include silicon, polycrystalline silicon, silicon oxide films, silicon nitrides, and metals such as Cu, W, Al, Ta, and TiN.

[0199] As a method for grinding a workpiece, one example is the method of grinding the surface of the workpiece using a grinding fluid (grinding slurry).

[0200] Examples of grinding slurries include metal barrier slurries, oxide film slurries, and Cu slurries. The slurry may contain abrasive particles, oxidants, protective components for the workpiece being ground, etchants, chelating agents, etc.

[0201] Examples of abrasive particles used as grinding agents in grinding slurries include silica (SiO2), alumina (Al2O3), and cerium dioxide (CeO2). Among these, silica is preferred, and colloidal silica is more preferred.

[0202] Furthermore, the grinding slurry can be acidic, neutral, or alkaline, but to prevent abrasive grain aggregation and facilitate abrasive grain dispersion, an acidic or alkaline slurry is preferred. Alkaline slurry is preferred. The liquid nature of the grinding slurry can be adjusted by adding acidic components such as sulfuric acid and phosphoric acid, alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide, organic alkali compounds such as tetramethylammonium hydroxide and choline, and alkaline components such as ammonia, as needed.

[0203] Example

[0204] The present invention will be described in more detail below through examples, but the present invention is not limited to these examples.

[0205] In all embodiments and comparative examples, unless otherwise specified, “%” means “mass %” and “parts” means “mass parts”.

[0206] <Example 1>

[0207] A resin-containing solution was obtained by adding 40 parts by mass of DMF, 2 parts by mass of an anionic surfactant composed of sodium alkyl sulfosuccinate (trade name: CRISVON Assister SD-11, manufactured by DIC Corporation), 2 parts by mass of acetyl cellulose (trade name: L-20, manufactured by Daicel Corporation), and 5 parts by mass of water to 100 parts by mass of a 100% ester-based polyurethane resin solution with a modulus of 5.9 MPa. The polyester-based polyurethane resin was obtained by condensing a polyester polyol (used without distillation, with a low molecular weight diol content of 12.9 mol%) obtained by dehydration condensation of 1,4-butanediol and adipic acid, a chain extender with a 1,4-butanediol / trimethylolpropane molar ratio of 60 / 40, and 4,4'-diphenylmethane diisocyanate (MDI). Next, a PET film is prepared as a film-forming substrate. The aforementioned resin-containing solution is coated onto the film using a doctor blade coater. The film is then immersed in a coagulation bath composed of water to allow the resin-containing solution to solidify. After solidification, the film is cleaned and dried to obtain a resin film. The skin layer formed on the surface of the obtained resin film is polished to a thickness of 100 μm to obtain a polyurethane sheet with a thickness of 0.80 mm. Then, a PET substrate is attached to the back of the polished surface using double-sided tape. The polished surface is embossed using a grid-shaped mold, and the unembossed surface is attached with double-sided tape containing release paper for fixing to the grinding platform to obtain a grinding pad.

[0208] <Example 2>

[0209] A resin-containing solution was obtained by adding 40 parts by mass of DMF, 2 parts by mass of an anionic surfactant composed of sodium alkyl sulfosuccinate (trade name: CRISVON Assister SD-11, manufactured by DIC Corporation), and 2 parts by mass of acetyl cellulose (trade name: L-20, manufactured by Daicel Corporation) to 100 parts by mass of a 100% ester-based polyurethane resin solution with a modulus of 5.9 MPa. The polyester-based polyurethane resin was obtained by condensing a polyester polyol (used without distillation, with a low molecular weight diol content of 12.9 mol%) obtained by dehydration condensation of 1,4-butanediol and adipic acid, a chain extender with a 1,4-butanediol / trimethylolpropane molar ratio of 60 / 40, and 4,4'-diphenylmethane diisocyanate (MDI). Next, a PET film is prepared as a film-forming substrate. The aforementioned resin-containing solution is coated onto the film using a doctor blade coater. The film is then immersed in a coagulation bath composed of water to allow the resin-containing solution to solidify. After solidification, the film is cleaned and dried to obtain a resin film. The skin layer formed on the surface of the obtained resin film is polished to a thickness of 150 μm to obtain a polyurethane sheet with a thickness of 0.95 mm. Then, a PET substrate is attached to the back of the polished surface using double-sided tape. The polished surface is embossed using a grid-shaped mold, and the unembossed surface is attached with double-sided tape containing release paper for fixing to the grinding platform to obtain a grinding pad.

[0210] <Example 3>

[0211] A resin-containing solution was obtained by adding 31.8 parts by mass of DMF, 4 parts by mass of a coagulation regulator composed of paraffin (trade name: CRISVON Assister SD-8i, manufactured by DIC Corporation), 2 parts by mass of a nonionic surfactant composed of a copolymer of ethylene oxide and propylene oxide (trade name: CRISVON Assister SD-21, manufactured by DIC Corporation), 2 parts by mass of acetyl cellulose (trade name: L-20, manufactured by Daicel Corporation), 5 parts by mass of diethylene glycol, and 5 parts by mass of pure water to 100 parts by mass of a 100% ester-based polyurethane resin solution with a modulus of 5.9 MPa (solid component concentration 30 by mass). As the polyester-based polyurethane resin, a polyurethane resin was obtained by condensing a polyester polyol (used without distillation, with a low molecular weight diol content of 12.9 mol%) obtained by dehydration condensation of 1,4-butanediol and adipic acid, a chain extender with a 1,4-butanediol / trimethylolpropane molar ratio of 60 / 40, and 4,4'-diphenylmethane diisocyanate (MDI). Next, a PET film was prepared as a film-forming substrate, and the above-mentioned resin-containing solution was coated onto it using a doctor blade coater. The film was then immersed in a coagulation bath composed of water, and after the resin-containing solution solidified, it was washed and dried to obtain a resin film. The skin layer side formed on the surface of the obtained resin film was polished to 150 μm to obtain a polyurethane sheet with a thickness of 0.80 mm. Then, a PET substrate is attached to the back of the polished surface using double-sided tape. The polished surface is then embossed using a grid-shaped mold. On the unembossed surface, double-sided tape with release paper is attached to fix it to the grinding platform to obtain a grinding pad.

[0212] <Comparative Example 1>

[0213] A resin-containing solution was obtained by adding 31.8 parts by mass of DMF and 5 parts by mass of water to 100 parts by mass of a 100% ester-based polyurethane resin solution with a modulus of 5.9 MPa (solids concentration 30% by mass). As the polyester-based polyurethane resin, a polyurethane resin was obtained by condensing a polyester polyol (used without distillation, low molecular weight diol content 12.9 mol%) obtained by dehydration condensation of 1,4-butanediol and adipic acid, a chain extender with a 1,4-butanediol / trimethylolpropane molar ratio of 60 / 40, and 4,4'-diphenylmethane diisocyanate (MDI). Next, a PET film was prepared as a film-forming substrate, and the above resin-containing solution was coated onto it using a doctor blade coater. The film was then immersed in a coagulation bath composed of water, and after the resin-containing solution solidified, it was washed and dried to obtain a resin film. The skin layer side formed on the surface of the obtained resin film was polished to 150 μm to obtain a polyurethane sheet with a thickness of 0.80 mm. Then, a PET substrate is attached to the back of the polished surface using double-sided tape. The polished surface is then embossed using a grid-shaped mold. On the unembossed surface, double-sided tape with release paper is attached to fix it to the grinding platform to obtain a grinding pad.

[0214] <Comparative Example 2>

[0215] A resin-containing solution was obtained by adding 31.8 parts by mass of DMF, 2 parts by mass of a coagulation regulator composed of paraffin (trade name: CRISVON Assister SD-8i, manufactured by DIC Corporation), 2 parts by mass of a nonionic surfactant composed of a copolymer of ethylene oxide and propylene oxide (trade name: CRISVON Assister SD-21, manufactured by DIC Corporation), 2 parts by mass of acetyl cellulose (trade name: L-20, manufactured by Daicel Corporation), and 5 parts by mass of pure water to 100 parts by mass of a 100% ester-based polyurethane resin solution with a modulus of 5.9 MPa (solid component concentration 30 by mass). As the polyester-based polyurethane resin, a polyurethane resin was obtained by condensing a polyester polyol (used without distillation, with a low molecular weight diol content of 12.9 mol%) obtained by dehydration condensation of 1,4-butanediol and adipic acid, a chain extender with a 1,4-butanediol / trimethylolpropane molar ratio of 60 / 40, and 4,4'-diphenylmethane diisocyanate (MDI). Next, a PET film was prepared as a film-forming substrate, and the above-mentioned resin-containing solution was coated onto it using a doctor blade coater. The film was then immersed in a coagulation bath composed of water, and after the resin-containing solution solidified, it was washed and dried to obtain a resin film. The skin layer side formed on the surface of the obtained resin film was polished to 150 μm to obtain a polyurethane sheet with a thickness of 0.80 mm. Then, a PET substrate is attached to the back of the polished surface using double-sided tape. The polished surface is then embossed using a grid-shaped mold. On the unembossed surface, double-sided tape with release paper is attached to fix it to the grinding platform to obtain a grinding pad.

[0216] <1. Pulse NMR Analysis>

[0217] The relaxation times and proportions of the crystalline, interfacial, and amorphous phases in a polyurethane sheet were determined using pulsed NMR as follows.

[0218] First, cut four 20×10mm pieces from the grinding pad. After peeling off the release paper on the back, bond the adhesive surfaces together to prepare two plate-shaped samples with both sides serving as grinding surfaces. Place a 1cm diameter glass tube filled with the two plate-shaped samples in a magnetic field. When measuring the macroscopic magnetization relaxation behavior after applying a high-frequency pulsed magnetic field, such as... Figure 2As shown, the free induction decay (FID) signal was obtained (horizontal axis: time (milliseconds), vertical axis: free induction decay signal). The initial value of the obtained FID signal is proportional to the number of protons in the sample. When there are three components in the sample, the FID signal is the sum of the response signals of the three components. On the other hand, due to the differences in the mobility of the components in the sample, the decay rate of the response signal is different between the components, and the spin-spin relaxation time T2 is different. Therefore, it is possible to separate them into three components by the least squares method, which are respectively identified as amorphous phase, interface phase, and crystalline phase in descending order of spin-spin relaxation time T2 (refer to...). Figure 2 Amorphous phases are components with high molecular mobility, while crystalline phases are components with low molecular mobility; the components in between are called interface phases.

[0219] After obtaining the FID signal, a fitting process is performed to separate the FID signal into signals for three components with different kinematic properties (crystalline phase, interface phase, and amorphous phase). In the fitting process, the BRUKER "TD-NMRAnalyzer" software is used. Following the product manual, the obtained relaxation curves are fitted using the following formula 1. The ratio and relaxation time of each component are calculated from the curves obtained from the measurements of the three components. The fitting is performed in two stages. First, as the first stage, the FID signal in the measurement time interval of 0.15–2.0 ms is fitted using a single component (i.e., only the amorphous phase component). The FID signal of the aforementioned single component (amorphous phase component) in the interval of 0–2.0 ms is calculated (the FID signal of the aforementioned single component (amorphous phase component) is also calculated for the interval of 0–0.15 ms through fitting). Next, as the second stage, the waveform obtained through the fitting in the first stage is subtracted from the overall FID signal of the three components within the measurement time interval of 0~2.0 ms. The subtracted waveform is then used as two components (i.e., the crystalline phase and the interface phase, which are the two components remaining after removing the amorphous phase from the crystalline phase, interface phase, and amorphous phase) for fitting. In this way, the FID signals of the crystalline phase and the interface phase can be separated from each other.

[0220] It should be noted that in this embodiment, the Weibull coefficients are set to W(1) = 2.0, W(2) = 1.0, and W(3) = 1.0 according to the relaxation time T2 from short to long for fitting.

[0221] In the first stage, the reason for fitting the FID signal in the measurement time range of 0.15~2.0 ms using only the amorphous phase composition is that the amorphous phase composition has a longer relaxation time compared to the crystalline phase composition and the interface phase composition (refer to...). Figure 2FID signals with a measurement time of 0.15 ms or longer are considered to originate from the amorphous phase component. In the second stage, by subtracting the waveform obtained in the first stage, FID signals consisting only of the crystalline phase and the interface phase are obtained. Therefore, by fitting these two components, the waveforms of the crystalline phase component and the interface phase component can be determined more accurately.

[0222] This analytical method, by dividing the number of components used for fitting and the analytical interval, can more effectively obtain the characteristics of amorphous phase components with long relaxation times.

[0223] Formula 1

[0224]

[0225] Here, I(t) represents the fitting strength at time t, a i T(n) represents the intensity factor of the nth component, T2(n) represents the relaxation time of the nth component, and W(n) represents the Weibull coefficient of the nth component.

[0226] (Sample preparation)

[0227] Dry sample:

[0228] The abrasive pads of Examples 1-3 and Comparative Examples 1-2 were cut into pieces of approximately 20×10mm. The release paper was peeled off, and the adhesive surfaces were glued together to prepare plate-shaped samples. The plate-shaped samples prepared from two pieces (four 20×10mm abrasive pads) were placed into a 10mmφ pulse NMR measurement sample tube as pulse NMR measurement samples.

[0229] Trimming the sample:

[0230] The 300mmφ polishing pads of Examples 1-3 and Comparative Examples 1-2 were placed on the platform of a single-sided polishing machine FAM 12BS (manufactured by SpeedFam Co., Ltd.). The polishing pads were then dressed using colloidal silica slurry and a 100mmφ diamond dresser (manufactured by 3M, model A188) under the following dressing conditions. Dressing was performed for 5, 15, 30, 60, 90, and 120 minutes respectively. The dressed polishing pads were then cut into approximately 20×10mm pieces, and the bonding surfaces were joined together to create plate-shaped samples. Two plate-shaped samples (four 20×10mm polishing pads) were placed into a 10mmφ pulse NMR sample tube as pulse NMR samples.

[0231] (Revision conditions)

[0232] Grinding machine used: SpeedFam, product name "FAM-12BS"

[0233] Platform rotation speed (grinding pad rotation speed): 30 rpm

[0234] Slurry: Colloidal silica slurry (using a mixture of pH: 11.5, colloidal silica stock solution (silica concentration 14~16wt%): water = 1:3 (mass ratio))

[0235] Flow rate: 80 mL / min (slurry is added dropwise from the center of rotation of the grinding pad)

[0236] Dressing tool: 3M diamond dressing tool, model "A188"

[0237] Dresser speed: 30 rpm

[0238] Dressing pressure: 10N

[0239] Test duration: 5, 15, 30, 60, 90, 120 minutes

[0240] (Relaxation time of amorphous phase components)

[0241] Samples that underwent trimming tests for 5, 15, 30, 60, 90, and 120 minutes (trimmed samples) and samples without trimming tests (dry samples) were subjected to pulsed NMR analysis using the method described in the "Pulse NMR Analysis" section above. The relaxation time of the amorphous phase component in samples trimmed for 5, 15, 30, 60, 90, and 120 minutes, as well as in the dry sample without trimming tests, was denoted as T. 2s,5min T 2s,15min T 2s,30min T 2s,60min T 2s,90min T 2s,120min T 2s,dry The relaxation times of Examples 1-3 and Comparative Examples 1-2 were determined. The results are shown in Table 1 and [Table data missing]. Figure 3 .

[0242] [Table 1]

[0243]

[0244] (Percentage of amorphous phase component (%))

[0245] For the polishing pads of Examples 1-3 and Comparative Examples 1-2, the proportion of amorphous phase components in the polishing pads at each trimming time was determined based on the method described in the "Pulse NMR Analysis" section above. The results are shown in Table 2 and... Figure 4 .

[0246] [Table 2]

[0247]

[0248] (ΔT 2s,15 ΔT 2s,120 SD(T) 2s,15-120min ))

[0249] For the abrasive pads of Examples 1-3 and Comparative Examples 1-2, ΔT was calculated using the obtained relaxation time results through the following formula. 2s,15min ΔT 2s,120min SD(T) 2s,15-120min The results are shown in Table 3.

[0250]

[0251] ΔT 2s,15min The relaxation time T of the amorphous phase component in a sample with a dressing time of 15 minutes. 2s,15min The relaxation time T of the amorphous phase component in the untrimmed sample 2s,dry difference

[0252] ΔT 2s,120min The relaxation time T of the amorphous phase component in a sample with a dressing time of 120 minutes. 2s,120min The relaxation time T of the amorphous phase component in the untrimmed sample 2s,dry difference

[0253] S.D.(T 2s,15-120min ) The relaxation time T of the amorphous phase component in samples with dressing times of 15 minutes, 30 minutes, 60 minutes, 90 minutes, and 120 minutes. 2s The obtained 5 relaxation times T 2s value deviation

[0254] [Table 3]

[0255]

[0256] (Amount of diethylene glycol)

[0257] In the abrasive pad of the present invention, in order to confirm that hydrophilic surfactants and polyol compounds are easily left in the resin sheet, the amount of diethylene glycol contained in the resin film after film formation in Example 3 and Comparative Example 1 was determined by the following method.

[0258] Approximately 270 mg of the resin membranes from Examples 3 and 1 (after film formation) were collected, and the weight of the collected resin was determined. The collected resin was then transferred to a vial and extracted with ethanol (3 mL ethanol, extracted by standing at 70°C for 6 hours using a hot plate).

[0259] Three collection and extraction operations were performed, yielding a total of approximately 9 mL of extract.

[0260] Ethanol was added to the obtained extract to prepare 10 mL. The extract with added ethanol was then diluted with acetone (HPLC-grade acetone with a small amount of tetradecane added (the amount that is somewhat close to the peak size of the target compound)) (extract:acetone = 2:1 (volume ratio)) to obtain the test sample.

[0261] The diethylene glycol (DEG) was quantified (mg) by gas chromatography-mass spectrometry (GC-MS) of the test sample prepared as described above. The results are presented below. Figures 10-11 .

[0262] It should be noted that the determination conditions based on gas chromatography-mass spectrometry are as follows.

[0263] [Device]

[0264] Gas Chromatography-Mass Spectrometry Analyzer: GC / MS-QP 2020 NX (manufactured by Shimadzu Corporation)

[0265] Sample injection device: AOC-20i Plus (manufactured by Shimadzu Corporation)

[0266] [Gas Chromatography Conditions]

[0267] Carrier gas: Helium

[0268] Column: DB-WAXetr (inner diameter 0.25mm, length 30m, film thickness 0.25μm)

[0269] Linear velocity: 36.1 cm / sec

[0270] Sample injection volume: 1 μL

[0271] Gas chromatograph injection port temperature: 250℃

[0272] Flow split ratio = 1:20

[0273] Column temperature program: Heating conditions are shown in Table 4.

[0274] [Mass Spectrometry Analysis Conditions]

[0275] Ionization method: Electron ionization method

[0276] Mass spectrometer interface temperature: 220℃

[0277] Scan range: m / z 29-350

[0278] Detection start time: 5 minutes after sample introduction

[0279] [Table 4]

[0280]

[0281] In the table, "-" does not specify a heating rate.

[0282] The DEG concentration in the resin was calculated by dividing the weight (mg) of a quantified amount of DEG by the total weight (g) of the collected resin. The results are shown in Table 5.

[0283] As shown in Table 5, the resin tablets of Example 3 contained a sufficient amount of DEG. It should be noted that a very small amount of DEG was also detected in Comparative Example 1, which is believed to be derived from the DEG contained in the raw materials.

[0284] [Table 5]

[0285]

[0286] <2. Grinding Test>

[0287] Using the polishing pads of each embodiment and comparative example, 120 silicon wafers with a TEOS (tetraethoxysilane) film and 120 silicon wafers with a Cu film were polished under the following conditions to evaluate polishing rate and defect performance.

[0288] (Grinding conditions)

[0289] Grinding machine used: Manufactured by Ebara Manufacturing Co., Ltd., trade name "F-REX300"

[0290] Grinding speed (platform speed): 70 rpm

[0291] Processing pressure: 176g / cm 2

[0292] Slurry flow rate: 200 mL / min

[0293] Dressing tool: 3M diamond dressing tool, model "A189L"

[0294] Adjustments: Ex-situ, 30N, 4 scans

[0295] Grinding time: 60 seconds

[0296] Materials to be ground: Silicon wafers with TEOS film and silicon wafers with Cu film

[0297] Grinding slurry: Colloidal silica slurry (using a mixture of pH: 11.5, colloidal silica stock solution (silica concentration 14~16wt%): water = 1:3 (mass ratio))

[0298] The grinding pad was placed on the grinding platform of the grinder. Before the grinding test, using slurry and a dressing device, the dressing pressure was 30 N, the rotation speed of the dressing device was 70 rpm, and the rotation speed of the grinding pad was 70 rpm. The dressing device and the grinding pad were rotated separately, and the slurry was dripped into the center of rotation of the grinding pad at a rate of 200 mL for 1 minute while the grinding pad was dressing for 30 minutes. Then, the following grinding test was carried out.

[0299] (Grinding rate)

[0300] For the TEOS film on the wafer before and after the grinding test, the average thickness was calculated from the thickness measurements at 121 points. The grinding rate (Å / min) was then determined by dividing the thickness measured at each point by the grinding time. It should be noted that the thickness was measured using an optical film thickness and quality measuring instrument (KLA Tencor, model "ASET-F5x", DBS mode). The results are shown in Table 6 and... Figures 5-8 It should be noted that, Figures 6-8 The left-hand arrow indicates the number of wafers required until the grinding rate stabilizes: 300 in Comparative Example 1, 150 in Comparative Example 2, and reduced to 50 in Examples 1-2. Figure 7 In Example 3, the number of pieces was reduced to 10. Figure 8 ).

[0301] [Table 6]

[0302]

[0303] Based on the obtained grinding rate results, determine the number of wafers required until the grinding rate stabilizes (number of wafers for initial processing), and evaluate them according to the following criteria. Set A+ and A as acceptable. The results are shown in Table 7.

[0304] Evaluation Criteria:

[0305] A+: The number of wafers processed at startup is 25 or less.

[0306] A: The number of wafers processed at startup is between 25 and 75.

[0307] B: The number of wafers processed at startup exceeds 75 but is less than 150.

[0308] C: The number of wafers processed at startup exceeds 150 but is less than 250.

[0309] D: The number of wafers processed at startup exceeds 250.

[0310] [Table 7]

[0311]

[0312] (Defect Performance Evaluation)

[0313] For the silicon wafers with Cu films after the above polishing tests, the high-sensitivity measurement mode of a surface inspection device (KLA Tencor, Surfscan SP5) was used to inspect the substrates numbered 2nd, 4th, 6th, 8th, 12th, 27th, 52nd, and 77th wafers for defects larger than 110 nm (surface defects such as scratches), and the number of defects was counted. The results are shown in Table 8 and... Figure 9 In addition, the performance evaluation of defects was conducted according to the following benchmarks, with A+ and A being considered acceptable. The results are shown in Table 8.

[0314] A+: The average number of defects on the surface of silicon wafers processed at the 2nd, 4th, 6th, 8th, 12th, 27th, 52nd, and 77th wafers is less than 20.

[0315] A: The average number of defects on the surface of silicon wafers processed at the 2nd, 4th, 6th, 8th, 12th, 27th, 52nd, and 77th wafers is between 20 and 40.

[0316] B: The average number of defects on the surface of silicon wafers processed at the 2nd, 4th, 6th, 8th, 12th, 27th, 52nd, and 77th wafers exceeds 40.

[0317] [Table 8]

[0318]

[0319] Regarding the results of the grinding tests, the grinding pads of Comparative Examples 1-2 showed a continuously increasing grinding rate from the initial grinding stage until the grinding of 300 or 150 wafers was completed, with a significant time required for the grinding rate to stabilize (poor start-up performance). Furthermore, the grinding pad of Comparative Example 1 generated numerous defects during startup. In contrast, the grinding pads of Examples 1-3 achieved a stable grinding rate after grinding approximately 50 wafers, and the time required for the grinding rate to stabilize was significantly shorter compared to Comparative Examples 1 and 2. Figures 7-8 The grinding pads of Examples 1-3 exhibit excellent start-up performance and excellent defect reduction performance. Furthermore, the grinding pads of Examples 1-3 demonstrate sufficiently high grinding rates and excellent grinding performance.

[0320] Industrial availability

[0321] According to the present invention, an abrasive pad with excellent start-up properties can be obtained. Therefore, the abrasive pad of the present invention is highly beneficial to industry.

Claims

1. An abrasive pad comprising a resin sheet having a plurality of teardrop-shaped air bubbles and an abrasive surface for abrading a workpiece. Using the least squares method, the spin-spin relaxation time T is obtained. 2s The long components are sequentially subtracted from the free induction decay signal FID obtained through pulsed NMR to perform waveform separation. Thus, according to the spin-spin relaxation time T... 2s The resin sheet is divided into three components from longest to shortest: amorphous phase, interface phase, and crystalline phase. In this case, for the resin sheet, the relaxation time T of the amorphous phase component of the resin sheet is determined by measuring the relaxation time using pulsed NMR after 15 minutes of conditioning of the polishing pad. 2s,15min The relaxation time T of the amorphous phase component of the resin sheet, obtained by measuring the relaxation time using pulsed NMR in the dry state before dressing the polishing pad. 2s,dry The difference is ΔT 2s,15min It is above 0.35ms.

2. The abrasive pad according to claim 1, wherein, The resin sheet is a polyurethane sheet.

3. The abrasive pad according to claim 1 or 2, wherein, The relaxation time T of the amorphous phase component was obtained by measuring the relaxation time using pulsed NMR at five time points: 15 minutes, 30 minutes, 60 minutes, 90 minutes, and 120 minutes, respectively, after the abrasive pad was conditioned. 2s The deviation of the value is SD(T) 2s,15-120min (less than 0.05ms) 4. The abrasive pad according to claim 1 or 2, wherein, The relaxation time T of the amorphous phase component, obtained by measuring the relaxation time using pulsed NMR, is given after 2 hours of conditioning of the abrasive pad. 2s,120min The relaxation time T of the amorphous phase component, obtained by measuring the relaxation time using pulsed NMR in the dry state before dressing the abrasive pad, is compared with that of the amorphous phase component. 2s,dry The difference is ΔT 2s,120min It is above 0.35ms.

5. The abrasive pad according to claim 1 or 2, wherein, When dressing the abrasive pad, the dressing time required for the relaxation time value of the amorphous phase component obtained from the relaxation time measurement using pulsed NMR to reach 0.8 ms or more is within 15 minutes.

Citation Information

Patent Citations

  • Polyurethane composition for polishing pad and polishing pad obtained using the same

    JP2007063323A

  • Urethane composition for polishing pad and polishing pad obtained using the same

    JP2007063324A

  • High planarization efficiency chemical mechanical polishing pads and methods of making

    JP2018043342A

  • Polishing pad and manufacturing method thereof

    JP2022156160A

  • Urethane resin composition and method for producing porous body

    JP2023044910A